Influence OF anticancer drugs on DNA methylation in liver of female mice - Hanafy, Shaden M.; Salem, Tarek A.; El-Aziz, Amal A.; EL-Fiky, Bahgat A.; Shokair, Mahmoud A. (Scientific Research Publishing, 2011)
Epigenetic changes such as DNA methylation regulate gene expression in normal development. Methotrexate and Adriamycine are antineoplastic drugs that target DNA and enzymes acting on DNA. We aimed to evaluate their cytotoxic effect on cell lines and on female mice to investigate the in vivo influence of both drugs on the DNA methylation and subsequently the protein expression. The total level of DNA methylation showed a significant reduction from 62.2% to 36.7%, 36.6% as compared to control group, when using different doses of MTX and ADR. Hepatic protein pattern revealed five bands with low MW (16 - 6.1 KDa) in acute and LD50 doses. In conclusion DNA methylation is influenced by anticancer drugs in a dose - dependent manner. Some specific protein fragments may be considered as a potential markers associated with high dose of anticancer drugs.
Keywords: Epigenetic; DNA Methylation; Methotrexate (MTX) and Adriamycine (ADR)